2017
DOI: 10.1177/1532673x17692325
|View full text |Cite
|
Sign up to set email alerts
|

Public Mood, Previous Electoral Experience, and Responsiveness Among Federal Circuit Court Judges

Abstract: Whether public opinion influences federal judges is a question that has long motivated—but often eluded—scholars. In this article, we examine two related questions: First, whether federal circuit court judges respond to circuit-level public opinion and, second, whether judges with extensive past elected political experience are even more responsive. The data show that circuit judges indeed respond to public opinion. The results also suggest that judges with greater past elected political experience may be more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“… Casillas et al (2011) suggest that public opinion exerts an important influence on Supreme Court decisions. Owens and Wohlfarth (2017) find similar results for federal circuit courts, despite both levels of Courts granting lifetime tenure. Indeed, legal scholars recognize the need for sentences to be neither too harsh nor too lenient because public trust in legal institutions is central to the legitimacy of the law ( Robinson 2013 ).…”
Section: Legitimacy Public Policy and Public Opinionsupporting
confidence: 53%
“… Casillas et al (2011) suggest that public opinion exerts an important influence on Supreme Court decisions. Owens and Wohlfarth (2017) find similar results for federal circuit courts, despite both levels of Courts granting lifetime tenure. Indeed, legal scholars recognize the need for sentences to be neither too harsh nor too lenient because public trust in legal institutions is central to the legitimacy of the law ( Robinson 2013 ).…”
Section: Legitimacy Public Policy and Public Opinionsupporting
confidence: 53%
“…Studies analyzing the US Supreme Court-where the justices have lifetime tenure-have shown that decisions in both criminal procedure and other types of cases are responsive to the first dimension of public policy mood (liberalism) (Casillas et al 2011, Erikson et al 2002a, McGuire & Stimson 2004). Owens & Wohlfarth (2017) have likewise found that federal circuit court judges follow circuit-level policy mood (liberalism) despite having lifetime tenure. Additionally, by influencing expected trial outcomes, public opinion may affect how prosecutors and defense attorneys present their cases to juries, which information cues they use, and whether prosecutors choose to pursue the death penalty (Baumgartner et al 2008).…”
Section: Mechanisms For Criminal Justice Representationmentioning
confidence: 92%